Access to maternal healthcare services among Indigenous women in the Chittagong Hill Tracts, Bangladesh: A cross-sectional study. Issue 10 (28th October 2019) - Akter, Shahinoor; Rich, Jane Louise; Davies, Kate; Inder, Kerry Jill
Abstract : Objectives: This study aimed to estimate the prevalence of, and factors associated with, accessing maternal healthcare services (MHC) by Indigenous women in the Chittagong Hill Tracts (CHT), Bangladesh. Design: This was a cross-sectional survey among Indigenous women of reproductive age. Setting: Two upazillas (subdistricts) of Khagrachhari hill district of the CHT. Participants: Indigenous women (15–49 years) within 36 months of delivery were surveyed about accessing MHC services (antenatal care, delivery and postnatal care) for their last pregnancy and delivery. Primary outcome measures: The primary outcome for this analysis is the prevalence of accessing any MHC service and secondary outcome is factors associated with access to MHC services for Indigenous women during their last pregnancy and childbirth. Results: Of 438 Indigenous women (220 Chakma, 100 Marma, 118 Tripura) who participated, 75% were aged 16–30 years. With an 89% response rate, a total of 258 (59%) women reported accessing at least one MHC service (Chakma 51.6%, Marma 28%, Tripura 20.5%; p=<0.001). Independent factors associated with accessing MHC after adjusting for clustering were attending secondary school and above (OR 2.4; 95% CI 1.2 to 4.9); knowledge about nearest health facilities (OR 3.8, 95% CI 1.8 to 7.8) and knowledge of pregnancy-related complications (OR 3.0, 95% CI 1.5 to 5.8). Conclusion: Findings suggest that the prevalence of accessing MHC services is lower among Indigenous women in the CHT compared with national average. MHC access may be improved through better education and awareness raising of local services.